Помогите с уравнением пожалуйста (СРОЧНО)

(x+2)*(x-3)*(x-1)=x(x+1)*(x+6)+6

И будьте так добры, распишите как решали

----------------------------------------------------------------------------------

Заранее Спасибо!

2

Ответы и объяснения

Лучший Ответ!
2012-11-13T22:44:38+04:00
2012-11-13T22:45:19+04:00

(x^2 - 3x +2 x - 6) (x - 1) = (x^2 + x) ( x + 6) + 6

(x^2 -x -6) (x-1) = ( x^3 + 6x^2 + x^2 +6x ) + 6

x^3 - x^2 - 6x -x^2 + x + 6 = x ^3 + 7 x^2 + 6x + 6

x^3 - 2 x^2 - 5x +6 = x^3 + 7x^2 +6x + 6

x^3 - 2x^2 - 5x +6 - x^3 - 7x^2 - 6x -6 = 0

-9x^2 - 11 x = 0

9x^2 + 11 x = 0

x * ( 9x +11 ) = 0

x=0 или 9x+11=0

             x= - 11/9  

Ответ : 0 ; -11/9